A sex-dependent role of Kv1.3 channels from macrophages in metabolic syndrome - Peraza, Diego A.; Benito-Salamanca, Lucía; Moreno-Estar, Sara; Alonso, Esperanza; López-López, José R.; Pérez-Garcia, M. Teresa; Cidad, Pilar (Frontiers in Physiology, 2024)
IntroductionCoronary artery disease (CAD) is the foremost single cause of mortality and disability globally. Patients with type 2 diabetes (T2DM) have a higher incidence of CAD, and poorer prognosis. The low-grade inflammation associated to T2DM contributes to increased morbidity and worst outcomes after revascularization. Inflammatory signaling in the vasculature supports endothelial dysfunction, leukocyte infiltration, and macrophage activation to a metabolic disease (MMe) specific phenotype, which could contribute to the metabolic disorders and ascular damage in T2DM. We have previously found that Kv1.3 blockers inhibit the development of intimal hyperplasia, thereby preventing restenosis. This inhibition was enhanced in a mouse model of T2DM, where systemic Kv1.3 blockers administration also improve metabolic dysfunction by acting on unidentified cellular targets other than vascular smooth muscle. Here we characterize the MMe phenotype in our T2DM model with a focus on macrophage Kv1.3 channels, to explore their contribution to vascular disease and their potential role as targets to ameliorate T2DM vascular risk.Methods and ResultsMale and female BPH mice fed on high-fat diet (HFD) develop metabolic syndrome (MetS) and T2DM. mRNA levels of several K+ channels (KV1.3, KCa3.1, Kir2.1) and macrophage markers (TNFα, NOS2, CD36) were analyzed. The MMe phenotype associated with increased CD36 expression. Channel-specific fingerprinting highlights a gender-specific increase of KV1.3 mRNA fold change in LPS stimulated macrophages from HFD compared to standard diet (SD). KV1.3 functional expression was also significantly increased after LPS stimulation in female HFD macrophages compared to SD. Functional studies showed that macrophage's KV1.3 channels of BPH female mice did not contribute to phagocytosis or metabolic profile but were relevant in cell migration rate.ConclusionAltogether, our data suggest that by inhibiting macrophage infiltration, Kv1.3 blockers could contribute to disrupt the vicious cycle of inflammation and insulin resistance, offering a novel approach to prevent MetS, T2DM and its associated cardiovascular complications in females.